2016
DOI: 10.1128/jvi.01188-16
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Neuraminidase Activity Exacerbates Disease in 2009 Pandemic Influenza Virus-Infected Mice

Abstract: During the first wave of the 2009 pandemic, caused by a H1N1 influenza virus (pH1N1) of swine origin, antivirals were the only form of therapeutic available to control the proliferation of disease until the conventional strain-matched vaccine was produced. Oseltamivir is an antiviral that inhibits the sialidase activity of the viral neuraminidase (NA) protein and was shown to be effective against pH1N1 viruses in ferrets. Furthermore, it was used in humans to treat infections during the pandemic and is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…However, we found that treatment with NA inhibitors had little-to-no effect on body weight loss and/or lung virus titers in mice infected with the NA inhibitor-sensitive virus (Figure 7). Similar findings were obtained with LPAI H7N9 and 2009 pandemic H1N1 viruses; mice infected with NA inhibitor-sensitive variants of these viruses and treated with NA inhibitors showed body weight loss (Ranadheera et al, 2016; Watanabe et al, 2013). Thus, the NA inhibitors may not provide effective treatment against the NA inhibitor-sensitive viruses of some influenza A virus subtypes in the mouse model.…”
Section: Discussionsupporting
confidence: 80%
“…However, we found that treatment with NA inhibitors had little-to-no effect on body weight loss and/or lung virus titers in mice infected with the NA inhibitor-sensitive virus (Figure 7). Similar findings were obtained with LPAI H7N9 and 2009 pandemic H1N1 viruses; mice infected with NA inhibitor-sensitive variants of these viruses and treated with NA inhibitors showed body weight loss (Ranadheera et al, 2016; Watanabe et al, 2013). Thus, the NA inhibitors may not provide effective treatment against the NA inhibitor-sensitive viruses of some influenza A virus subtypes in the mouse model.…”
Section: Discussionsupporting
confidence: 80%
“… 43 , NA stalk truncation might reduce the structural flexibility of NA enzymatic pocket, and, as a result, it would restrain NA affinity for its substrate. Similar to a limited access theory of short stalk NAs 34 , 44 , 45 , the flexibility constraint of NA enzymatic pocket caused by NA stalk truncation 43 and the reduction of NA enzymatic activity due to antiviral treatment 46 also suggested the increase of viral pathogenicity. When the NA stalk mutations applied to the NA of H7N9 vaccine virus, based on the sequence alignment with the N1 subtype NA protein, the rH7N9/NA:Δ57–65 and rH7N9/NA:N63T viruses also exhibited enhanced viral pathogenicity in mice (Figs 8 and 9 ).…”
Section: Discussionmentioning
confidence: 64%
“…The balance between HA and NA proteins contributes to expression of the HPAI phenotype ( Diederich et al, 2015 ). Furthermore, the NA gene has been shown to play an important role in influenza virus enzyme activity, transmission, and pathogenicity ( Lv et al, 2015 ; Stech et al, 2015 ; Ranadheera et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%